Modeling MOSFETs by using C++ - Roy Stephen, Joel Jimbai. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The Metal Oxide Semiconductor Field - Effect Transistors (MOSFET) has become by far the most widely used electronic devices, especially in the design of integrated circuits (ICs), which are circuits fabricated on a single silicon chip. The reason for the label metal-oxide- semiconductor FET is: metal for the drains source and gate connection to the proper surface - in particular, the gate terminal and the control to be offered by the surface are of the contact, structure on which the n-and p-type regions are diffused. Thus, in this paper, the characteristics of the MOSFETs are briefly discussed at which one of the objectives is to model these characteristics by using software, Microsoft Visual C++ and in this project, the drain characteristics of both NMOS and PMOS is modelled . As goes further this paper, the created C++ programming for the inverter which are then further implement to verify the operation of pairs of gate logics ; AND/NAND, OR/NOR and XOR/XNOR and also Half - Adder. Nevertheless, the constraints faced by the author are concluded and few recommendations are suggested for future apprentices.